N.E. Thing Co. Ltd. : Companies Act (Volume 1) - Ammann, Jean-Christophe; Baxter, Iain (Vancouver : [s.n.], 1978)
Full page black and white reproductions of various N.E. Thing Co. projects, archival documents, and "visual sensitivity information."
uitgegeven in eigen beheer
boek
Keywords: N.E. Thing Co. Ltd